Excavations at Tatev monastery in 2014-2015 - Melkonyan, Husik; Harutyunyan, Arsen; Davtyan, Davit (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
According to the tradition the monastery of Tatev settled on the very edge of the Vorotan river gorge (Figures 1/1-2, 2/1) was founded in early Middle Ages and took its name after Eustatheus, disciple of St. Thaddeus the Apostle. In accordance with historiographer Step‘anos Orbēlean: ‘And on a highest rock in that area there was an obscure church built in very ancient times of huge rough stones fastened by lime mortar and dedicated to St. Nerses and St. Sahak; a small fraternity practicing permanent asceticism had been inhabiting there…’.